Zakat Philanthropy and Power: Critical Discourse Analysis of BZNAS Disaster Response Narratives in Indonesia - Rahmat, Wahyudi; Tiawati, Refa Lina; Cesaria, Anna; Zulfa, Zulfa; Tatalia, Ricci Gemarni; Azri, Harizqi; Mujtaba, Sultan Tirta; Rahmad, Hari Adi (Ranah: Jurnal Kajian Bahasa, 2025)
This study investigates how the National Amil Zakat Agency (BAZNAS) constructs its institutional image and legitimacy in disaster management through discourse. Using Teun A. van Dijk’s Critical Discourse Analysis (CDA) framework, the research explores textual, cognitive, and contextual dimensions of BAZNAS’s disaster response narratives. The study analyzes official publications, press releases, and media reports to reveal how language is strategically employed to shape public perception of BAZNAS as both a faith-based and professional humanitarian actor. The findings demonstrate that BAZNAS incorporates Syariah legitimacy (endorsed by the Indonesian Ulema Council's Fatwa No. 66/2022), technocratic legitimacy (achieved through ISO 9001:2015 certification and unqualified audit opinions), and political legitimacy (via endorsements from State officials). These layers of discourse position BAZNAS as a quasi-state institution bridging religious duty and bureaucratic professionalism. At the superstructural level, narratives emphasize rapid response, organizational efficiency, and structured governance, while micro-level analysis highlights rhetorical strategies such as quantification, metaphors of heroism, and digital transparency that reinforce credibility and public trust. This study concludes that BAZNAS’s discourse transforms the meaning of Zakat from a traditional act of charity into a modern instrument of disaster governance and social resilience. By linking faith-based values with managerial and state-endorsed frameworks, BAZNAS strengthens its role as a central actor in Indonesia’s philanthropic ecosystem. The research contributes to the understanding of Islamic philanthropy, discourse, and power relations in the context of humanitarian crises. Abstrak Penelitian ini menginvestigasi bagaimana Badan Amil Zakat Nasional (BAZNAS) membangun citra kelembagaan dan legitimasi dalam penanggulangan bencana melalui wacana. Dengan menggunakan kerangka Analisis Wacana Kritis (AWK) Teun A. van Dijk, penelitian ini mengeksplorasi dimensi tekstual, kognitif, dan kontekstual dari narasi respons bencana BAZNAS. Studi ini menganalisis publikasi resmi, siaran pers, dan laporan media untuk mengungkap bagaimana bahasa digunakan secara strategis dalam membentuk persepsi publik terhadap BAZNAS sebagai aktor kemanusiaan yang berbasis keagamaan sekaligus profesional. Temuan penelitian menunjukkan bahwa BAZNAS menggabungkan legitimasi Syariah (diperkuat oleh Fatwa Majelis Ulama Indonesia No. 66/2022), legitimasi teknokratis (melalui sertifikasi ISO 9001:2015 dan opini audit tanpa pengecualian), serta legitimasi politik (melalui dukungan pejabat negara). Lapisan-lapisan wacana tersebut memosisikan BAZNAS sebagai lembaga kuasi-negara yang menjembatani kewajiban keagamaan dengan profesionalisme birokratis. Pada tataran superstruktur, narasi menonjolkan respons cepat, efisiensi organisasi, dan tata kelola yang terstruktur; sementara analisis pada level mikro menyoroti strategi retoris seperti kuantifikasi, metafora heroisme, dan transparansi digital yang memperkuat kredibilitas dan kepercayaan publik. Penelitian ini menyimpulkan bahwa wacana BAZNAS mentransformasikan makna zakat dari sekadar tindakan amal tradisional menjadi instrumen modern tata kelola bencana dan ketangguhan sosial. Dengan mengaitkan nilai-nilai keagamaan dengan kerangka manajerial dan dukungan negara, BAZNAS memperkuat perannya sebagai aktor sentral dalam ekosistem filantropi di Indonesia.